QUALITY OF HUMAN RESOURCE INFORMATION SYSTEMS AT COMMERCIAL BANK OF ETHIOPIA (A CASE STUDY OF DESSIE DISTRICT AT DESSIE, ETHIOPIA) - SB, Ponduri (International Journal of Research -GRANTHAALAYAH, 2016)
Information systems are the back bones of every organization in the modern era of business management. It is inevitable for these organizations to use information system so as to face the global competition and survive in the market. No organization and country is an exception to it. Human resources management is one of the crucial departments in every organization that uses management information systems. HR information systems help to identify potential employees, maintaining complete records on existing employees and creating programs to develop employee skills and talents. This helps the top level management to identify the future manpower requirements in order to meet the long term goals and objectives, middle level management to monitor, analyze the recruitment, promotion, allocation and compensation and lower level management to track the recruitment and placements. HRIS can also support various human resource practices such as workforce planning, staffing, salary, compensation forecasts, budgets and industrial relations. The current research is mainly focused on human resource information systems (HRIS) perception and effectiveness. The required data was collected through primary and secondary sources. The research approach is both quantitative and qualitative. A sample of 100 respondents working in different department of commercial bank of Ethiopia, Dessie district were taken for the study. The findings of this research results in employees are satisfied with salary, job position, promotion scheme, and working environment but worried about the system about information sharing of human resource and their difficulty to store, retrieve, share and maintain information.